Lung cavitation-a rare complication in COVID-19 patients: A case report - Bhoomi Angirish; Ketan Parmar (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Background: Usually, in clinically cured patients with viral pneumonia, the pulmonary lesions gradually resolve and show complete remission. In very few severe patients, there are residual lesions and fibrosis. Since SARS-CoV-2 is a new disease, the healing process of infected pulmonary lesions is not well known and is variable.  Case presentation: This is a case report of a 51 year old COVID-19 infection patient, who initially presented with ground glass opacities and consolidation but eventually developed large pulmonary cavity and fibrosis in the involved lobes during the course of disease. Conclusion: Most of the patients infected with SARS-CoV-2 show near complete resolution of the lesions with mild residual opacities, however few patients develop complications in the course of disease.